2023
DOI: 10.3389/fimmu.2023.1140791
|View full text |Cite
|
Sign up to set email alerts
|

The crosslinks between ferroptosis and autophagy in asthma

Abstract: Autophagy is an evolutionarily conserved cellular process capable of degrading various biological molecules and organelles via the lysosomal pathway. Ferroptosis is a type of oxidative stress-dependent regulated cell death associated with the iron accumulation and lipid peroxidation. The crosslinks between ferroptosis and autophagy have been focused on since the dependence of ferroptosis on autophagy was discovered. Although the research and theories on the relationship between autophagy and ferroptosis remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 203 publications
(211 reference statements)
0
4
0
Order By: Relevance
“…In recent years, potential cross-linking between ferroptosis and autophagy has been found in a variety of cells treated with various compounds. 91 Further studies have found that the cross-linking of ferroptosis and autophagy may be closely related to a variety of signaling pathways. 92 Single inhibition of ferroptosis or autophagy can reverse the negative effects of compounds on cells.…”
Section: Potential Cross-linking Pathways Between Autophagy and Ferro...mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, potential cross-linking between ferroptosis and autophagy has been found in a variety of cells treated with various compounds. 91 Further studies have found that the cross-linking of ferroptosis and autophagy may be closely related to a variety of signaling pathways. 92 Single inhibition of ferroptosis or autophagy can reverse the negative effects of compounds on cells.…”
Section: Potential Cross-linking Pathways Between Autophagy and Ferro...mentioning
confidence: 99%
“…The relationship between the two needs to be clarified. In recent years, potential cross‐linking between ferroptosis and autophagy has been found in a variety of cells treated with various compounds 91 . Further studies have found that the cross‐linking of ferroptosis and autophagy may be closely related to a variety of signaling pathways 92 .…”
Section: Potential Cross‐linking Pathways Between Autophagy and Ferro...mentioning
confidence: 99%
“…[17][18][19][20] Moreover, accumulating evidence suggest that lysosomes are not only participants in the autophagy process, but also vital iron storage hubs in cells. [21][22][23][24][25][26] For instance, ferritinophagy, the autophagic degradation of ferritin, triggers the release of iron in lysosomes. 27 Moreover, lysosomal dysfunction can induce lysosomal membrane permeabilization (LMP), resulting in the release of considerable iron into the cytoplasm, further enhancing cell-intrinsic Fenton chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Asthma is a chronic inflammatory disease (1) with an increasing prevalence affecting approximately 262 million in 2019, and it was responsible for 21.6 million disability-adjusted life years (DALYs) in the same year (2). Clinical symptoms are recurring breathlessness and wheezing accompanied by airway obstruction, bronchial hyperresponsiveness, and airway inflammation (3).…”
Section: Introductionmentioning
confidence: 99%